Efektifitas Budaya Organisasi, Teknologi Informasi terhadap Kualitas Sistem Informasi Akuntansi - Puspitawati, Lilis (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
This study aims to determine how much influence Organizational Culture and Information Technology has on the Quality of Accounting Information Systems. This research was conducted by distributing questionnaires to companies that were used as research samples. The unit of analysis in this study is the car dealer located in Bandung. The method used in this study uses descriptive methods and verification method. The sampling method in this study is using a probability sampling technique with a simple random sampling approach. Data analysis using multiple linear regression, while for testing the hypothesis in this study using t test statistics using software SPSS 20. From the coefficient of determination obtained the value of the Organizational Culture of 37,45% and the value of Information Technology 60,52%. The results of this study indicate that Organizational Culture does not have a significant effect on the Quality of Accounting Information Systems, while Information Technology has a significant effect on the Quality of Accounting Information Systems